Pattern of Community Economic Empowerment in Slump Area in Mojo Village - Bambang S. Pujantiyo (Universitas Negeri Malang, 2025)
Physical reorganization programs in some slum areas have been carried out massively by the government, but there has been no initiative to empower the community's economy, so it is very important to know how the pattern is being carried out independently. This study aims to analyze the pattern of community economic empowerment, especially related to community income as a result of physical reorganization in the Mojo slum area in Surakarta city. However, until now there has been no analysis of the income of the Mojo community after the implementation of the physical reorganization program. So to be able to find out, a qualitative descriptive methodology is used by collecting data through document studies and interviews with stakeholders and local communities. Based on secondary data and observations, an analysis of life sustainability was carried out using pentagonal assets, so that reliable assets could be known, and from the interview results it was known the impact on community income and empowerment patterns. As a result, it can be seen that in the pattern of implementing community empowerment independently, the role of intermediaries is very dominant, and in the end can provide resilience in the income level of the community. So it can be said that the increase in community income as one of the indicators in the economic empowerment of the community in Mojo is strongly influenced by the pattern and important role of intermediaries.